Bubble Fusion Research Under Scrutiny. - Guizzo, E. (IEEE spectrum)
This paper reports on the controversy surrounding a new method of achieving fusion by imploding bubbles in a liquid. Called bubble fusion or sonofusion, it was discovered by a team of researchers led by Purdue University professor, Rusi P. Taleyarkhan. While many experts believe that making hydrogen nuclei fuse in imploding bubbles is possible in principle, they are not convinced that this was actually achieved by Taleyarkhan. They are concerned whether Taleyarkhan's group has ruled out possible sources of errors in detecting the neurons that are characteristic fusion signature. So far, no independent group has been able to replicate the experiment